The possibilities of text mining in the examination of the local society of the Ormánság region - Hornyák, Miklós; Ragadics, Tamás (Marketing & Menedzsment, 2017)
THE AIMS OF THE PAPER This paper aims to represent the background of the consumer behaviour in families from underprivileged strata living in small settlements of the Ormánság region. METHODOLOGY Our diagnoses are based on interviews with mayors. We use text mining methods for deeper analysis of the interviews and present results with different visualization techniques. With the help of comparative word clouds, we performed the support of the examination of settlement clusters created through using the quantitative data. MOST IMPORTANT RESULTS According to our experimental work, the method is suitable for making the results of interview research more targeted, sophisticated and to demonstrate the results. Our experiences gathered in the course of the research indicated the importance of the size of the corpus, and the necessity of using specific knowledge when supporting sociological research with text mining. RECOMMENDATIONS Ormánság micro region (South Transdanubia, Hungary) is characterized by a frittered settlement structure, low economic figures, and disadvantageous social processes. Adult members of families living in the culture of poverty are not able to deliver the patterns and motivation for social and economic advancement for their children, neither the values or norms for the conventional organizing of everyday life. Illogical consumer habits (“Carpe diem” mentality, commercial credit, purchasing status symbols etc.) are deepening the social gap and segregation and confining the accidental chances for self-care. Complex supporting system is necessary with the elements of labour market incentives, consulting, mentoring and development of competencies.